Effects of microclimate factors on the distribution of Araceae in Kinabalu Park, Sabah, Borneo, Malaysia - RASYIDAH WAHAB; KARTINI SAIBEH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Wahab R, Saibeh K. 2025. Effects of microclimate factors on the distribution of Araceae in Kinabalu Park, Sabah, Borneo, Malaysia. Biodiversitas 26: 3237-3245. The growth and distribution of plant species, such as Araceae, in Kinabalu Park, Sabah, Borneo, Malaysia, are influenced by the microclimatic conditions of their habitat. These microclimatic variations result from the combined effects of environmental factors, including temperature, humidity, and light intensity. Therefore, this study examined how microclimatic factors influence the habitat preferences of Araceae in Kinabalu Park through transect sampling along major trails across seven study areas. It revealed a high diversity of Araceae, with 88 species from 17 genera identified, belonging to eight tribes. The tribe Schismatoglottideae and genus Schismatoglottis were the most represented. While, the most abundant species was Homalomena sagittifolia. Species turnover was low to moderate across the study areas, as indicated by the Jaccard similarity index (23.08-56.10%). Canonical Correspondence Analysis showed that microclimatic factors significantly influenced the species distribution, with an inertia value of 84.96%. Correlation values indicated that temperature (r2: 0.8898) and relative humidity (r2: -0.8764) were the most significant factors. In conclusion, the Araceae species in Kinabalu Park exhibit strong adaptability to microclimatic variations driven by its complex topography. This observation underscores the ecological significance of microhabitats in promoting the diversity of Araceae species, highlighting the need for conservation strategies that account for these environmental interactions.